Road Traffic Injuries : A Public Health Crisis in MENA - Dahdah, Said (World Bank, Washington, DC, 2014)
The Middle East and North Africa (MENA) has made dramatic progress in lowering premature death and disability from most communicable, newborn, nutritional, and maternity causes. However, non-communicable diseases are still extremely high. Road traffic injuries, for example, are the fourth leading cause of death in MENA. Compared to other developing countries, the composition of road injury deaths in the MENA region is much greater. This brief sheds light on the occurrences of such road injuries in MENA, and the possible measures to reduce the frequency of these occurrences.